MINERALOGY, GEOCHEMISTRY AND ECONOMIC POTENTIAL OF ZIRCON AND ASSOCIATED MINERALS IN DUBAYDIB SANDSTONE FORMATION, JORDAN - Ahmad Al-Malabeh (Iraqi Geological Journal, 2017)
This study was conducted to evaluate the zircon minerals in Wadi Al-Mezrab, South Jordan. Zircon at the study area belongs to the Middle member of the Dubaydib Formation of the Middle Ordovician age. The detailed petrographic study shows that the host rock is composed mainly of quartz, plagioclase, biotite, muscovite, and zircon, with small amounts of other heavy minerals such as rutile, tourmaline and monazite. The samples are composed of magnetic minerals that range in concentrations from 6.2% to 42% and non-magnetic range between 58% and 93.8%. The gravity separation using heavy liquids showed that the heavy minerals averages about 10%. Zircon grains are mostly clear, euhedral to rounded grains and exhibit elongated or stubbed prisms. Chemical analytical data indicate that the average content of Zr is 2.4%, Ce, La and Y percentages (in monazite) are 7.1%, 1.9% and 0.04%, respectively in concentrated samples and TiO2 content is 6.8%. The results indicate positive relationships between the Zr, Ce, La, Y, and TiO2. The highest percentage of Zr, TiO2, and REE in non-magnetic mineral concentrates within the size fractions of less than 75 + 45 to -45 μm. The calculated result of % by weight showed; the highest content of Zr was 22.82, the ZrO2% was 32, and the ZrSiO4% was 49.14 of the less than 75 to 45 size fraction.